OCCURRENCE OF THE FORK-TAILED HUMMINGBIRD Eupetonema macroura (GMELIN, 1788) IN THE CENTRAL SOUTHERN PARANÁ STATE, BRAZIL: OBSERVATIONS OF DISPERSION - Vogel, Huilquer Francisco; Valle, Luis Gustavo Eckhardt; Metri, Rafael; Zawadzki, Cláudio Henrique (SaBios-Revista de Saúde e Biologia, 2010)
O presente estudo trata do primeiro registro em literatura do beija-flor-tesoura Eupetonema macroura (Gmelin, 1788), espécie localizada em Guarapuava e na região Centro-Sul do Paraná. A espécie apresenta rápida capacidade para colonizar novos ambientes, principalmente áreas urbanas e ou fragmentadas, obtendo vantagens na utilização da vegetação alterada ou exótica. Mais estudos são necessários sobre a ecologia do mesmo e o papel deste na estruturação de comunidades regionais de beija-flores do Estado do Paraná. ABSTRACT <div style="border-bottom: #003366 2.25pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0cm; padding-right: 0cm; border-top: medium none; border-right: medium none; padding-top: 0cm; mso-element: para-border-div;"> This report is the first documented record in literature concerning to Fork-tailed Hummingbird Eupetonema macroura (Gmelin, 1788), a species located in Guarapuava city and South-Central region of Paraná State. This species has the ability to rapidly colonize new environments, mainly in urban and fragmented areas, by taking advantage of its ability to explore modified and exotic vegetation. Further researches are needed to investigate its recent role in the regional community structure of the hummingbirds from the Paraná State.